Does the transfer of knowledge from the pioneer generation to the second‐generation speed‐up the learning curve of robot‐assisted partial nephrectomies? TRANSFER trial (UroCCR n°83) - Louis Vignot; Zine‐Eddine Khene; Adil Mellouki; Arnoult Morrone; Jean‐Christophe Bernhard; Karim Bensalah; Daniel Chevallier; Nicolas Doumerc; Morgan Roupret; Francois‐Xavier Nouhaud; Cédric Lebacle; Jean‐Alexandre Long; et al. (BJUI Compass)
Abstract Objectives The objective is to compare the learning curves between two pioneer and three second‐generation surgeons for RAPN in terms of WIT, CD and positive surgical margins. Materials and methods The charts of consecutive RAPNs of three centres were reviewed from the UroCCR prospective database. The experience was assessed by a regression model for each group. There was a univariate analysis on three consecutive sequences of 15 procedures. The learning speed for WIT was explored graphically by polynomial regression after cubic splines. Finally, CUSUM charts were obtained. Results There were 1203 RAPN in the pioneer group and 119 performed by second‐generation surgeons. There was a significant difference in the distribution of tumour size (p < 0.001) and the RENAL score (p < 0.001). The operative time was longer in the first group (p > 0.001). Independent factors for a higher WIT were the second group (p < 0.001), higher experience (p < 0.001) the collinearity between the group and experience (p < 0.001), the RENAL score (p < 0.001) and blood loss (p < 0.001). Adjusted Loess regressions showed a plateau of WIT at 400 procedures for the pioneers and a significant decrease at 20 procedures for the second generation. CUSUM chart analysis showed a ‘staircase’ pattern of the learning process, with three major steps at 150, 200 and 300 procedures. The major limitation is the difference in sample size between the two arms. Conclusions Learning curve patterns would reflect a transfer of knowledge to the second‐generation, as opposed to the establishment of standards by the pioneers.